Hedgerow structural diversity is key to promoting biodiversity and ecosystem services: A systematic review of Central European studies - Kratschmer, Sophie; Hauer, Julia; Zaller, Johann G.; Dürr, Alexandra; Weninger, Thomas (Basic and applied ecology, 2024)
•Relations among hedgerow structure, biodiversity & ecosystem services are unclear.•We performed a systematic review including 89 studies from Central Europe and UK from 1974 to 2022.•Arthropods & birds, were most often, earthworms & bats least often studied.•Structural diversity, layering & woody vegetation promoted biodiversity.•Connectivity, density & structural complexity improved ecosystem service provision. Agricultural intensification decreases the heterogeneity of the landscape and leads to a decline in hedgerows. As hedgerows provide important habitats for many taxa, this contributes to the loss of biodiversity in agroecosystems. However, the extent to which hedgerows, and in particular their habitat quality in terms of structural characteristics, also influence biodiversity-based ecosystem services is poorly studied. Here, we conducted a systematic review of the Scopus and other literature databases focusing on Central European and UK studies examining (1) the influence of hedgerow habitat quality on the biodiversity of arthropods, earthworms, birds, bats and small mammals and (2) the relationship between selected hedgerow parameters, animal taxa, and ecosystem services such as pollination, seed dispersal, pest and disease control and soil quality regulation. A total of 2260 studies (cut-off date: 13 September 2022) published between 1974 and 2022 were found. After sorting based on inclusion criteria related to the research focus, 89 studies remained for evaluation. Arthropods, birds, and small mammals were studied most frequently, earthworms and bats least frequently. The selected studies showed that structural diversity, layering, woody biomass and density were strongly positively correlated with animal species diversity, while hedgerow length, width and age showed less relevant relationships. Hedgerow connectivity, density, structural diversity, and layering were strongly positive associated with the provision of ecosystem services. We conclude that the structural diversity of hedgerows needs to be increased if their impact on biodiversity and ecosystem service provision is to be improved. It is therefore recommended that hedgerow management measures should specifically consider the ecological importance of the structural diversity of hedgerows.